2022
DOI: 10.2196/41241
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between QT and Corrected QT Interval Assessment by an Apple Watch With the AccurBeat Platform and by a 12‑Lead Electrocardiogram With Manual Annotation: Prospective Observational Study

Abstract: Background Abnormal prolongation or shortening of the QT interval is associated with increased risk for ventricular arrhythmias and sudden cardiac death. For continuous monitoring, widespread use, and prevention of cardiac events, advanced wearable technologies are emerging as promising surrogates for conventional 12‑lead electrocardiogram (ECG) QT interval assessment. Previous studies have shown a good agreement between QT and corrected QT (QTc) intervals measured on a smartwatch ECG and a 12-lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Moderate agreement, defined as d <40 ms, was found in 86% of the QT intervals and 74.4% of the QTc measurements. Chokshi et al ( 40 ) compared the SW-recorded QT and QTc assessed using AccurKardia's AccurBeat platform with the conventional 12-lead ECG. This study consisted of 50 healthy participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderate agreement, defined as d <40 ms, was found in 86% of the QT intervals and 74.4% of the QTc measurements. Chokshi et al ( 40 ) compared the SW-recorded QT and QTc assessed using AccurKardia's AccurBeat platform with the conventional 12-lead ECG. This study consisted of 50 healthy participants.…”
Section: Resultsmentioning
confidence: 99%
“…A cardiology-focused digital health company (AccurKardia) had developed a device diagnostic platform (AccurBeat) to analyze Apple Watch-generated ECGs. It was found that a total of 94% of the average QT interval measurements by the platform and the 12-lead ECG were within the 95% CI of the average difference ( 40 ). Some studies have shown that manual measurement is even more accurate ( 48 ).…”
Section: Discussionmentioning
confidence: 99%